The Indigeneity Clause and the Mismanagement of Ethnic Diversity in Nigeria - Gbeke Adenuga (Dynamics of Politics and Democracy, 2022)
Purpose: Nigeria is characterized by ethnic diversity and the quest to achieve ‘unity in diversity’ led to its adoption of federalism as the basic structure and principle of governance. Over six decades after independence, the country remains sharply divided along ethnic lines, and national unity remains a mirage. While there is a burgeoning body of research on the causes, manifestations, and consequences of ethnic diversity mismanagement in Nigeria, few attempts have been made to analytically study the effects of constitutional provisions on the phenomenon. The study, thus, examined the effects of the indigeneity clause in the Nigerian constitution on ethnic diversity management in the country. Research methodology: The study is based on a review of secondary data on Nigeria’s constitutional provisions and institutional processes. Results: It identified that the indigeneity clause in the country’s constitutions has created different notions of citizenship and further exacerbated differences between ethnic groups in the country. The clause established two classes of Nigerians, indigenes, and settlers, and the ensuing ‘us against them’ culture lies at the root of ethnic tensions witnessed in the country. Limitations: Other issues, apart from the indigeneity clause, may also lead to the mismanagement of ethnic diversity in the country. Contribution: The findings and recommendations of the study provide a veritable template to help ensure good ethnic diversity management in Nigeria and other multi-ethnic states.